Clustering and superspreading potential of SARS-CoV-2 infections in Hong Kong - Adam, Dillon C.; Wu, Peng; Wong, Jessica Y.; Lau, Eric H. Y.; Tsang, Tim K.; Cauchemez, Simon; Leung, Gabriel M.; Cowling, Benjamin J. (Nature Medicine, 2020)
Superspreading events (SSEs) have characterized previous epidemics of severe acute respiratory syndrome coronavirus (SARS-CoV) and Middle East respiratory syndrome coronavirus (MERS-CoV) infections 1 – 6 . For SARS-CoV-2, the degree to which SSEs are involved in transmission remains unclear, but there is growing evidence that SSEs might be a typical feature of COVID-19 7 , 8 . Using contact tracing data from 1,038 SARS-CoV-2 cases confirmed between 23 January and 28 April 2020 in Hong Kong, we identified and characterized all local clusters of infection. We identified 4–7 SSEs across 51 clusters ( n = 309 cases) and estimated that 19% (95% confidence interval, 15–24%) of cases seeded 80% of all local transmission. Transmission in social settings was associated with more secondary cases than households when controlling for age ( P = 0.002). Decreasing the delay between symptom onset and case confirmation did not result in fewer secondary cases ( P = 0.98), although the odds that an individual being quarantined as a contact interrupted transmission was 14.4 (95% CI, 1.9–107.2). Public health authorities should focus on rapidly tracing and quarantining contacts, along with implementing restrictions targeting social settings to reduce the risk of SSEs and suppress SARS-CoV-2 transmission. Cases linked to superspreading events are estimated to account for 80% of all local transmission of SARS-CoV-2 in Hong Kong in a study with implications for public health policies.